Biomass and nutrient composition of temperate mangroves (Avicennia marina var. australasica) in New Zealand. Issue 3 (3rd July 2017) - Tran, Phan; Gritcan, Iana; Cusens, Jarrod; Alfaro, Andrea C.; Leuzinger, Sebastian
ABSTRACT: Accurate estimates of biomass pools and their nutrient content are key for assessing the potential of vegetation to mitigate anthropogenic carbon emissions. In this study, we used the harvest method to estimate above- and below-ground biomass (AGB and BGB) and nutrient content of the New Zealand mangrove Avicennia marina var . australasica at Mangawhai Harbour, northern New Zealand. AGB of A. marina was estimated at 5.7 ± 1.79 kg m −2 and BGB at 13.15 ± 1.55 kg m −2 (mean ± SE). The root-shoot ratio at this site was 1.73. Fine roots contributed most to the total biomass (37%) followed by woody biomass (32%), coarse roots (27%), leaves (3%), and pneumatophores and seedlings (1%). Allocation of total carbon (TC) followed similar proportions as total biomass with was 64% in the roots, 33% in wood, and 3% in the leaves (by dry mass). Roots contained 64% of total nitrogen (TN) and 53% of total phosphorus (TP) (by dry mass). In leaves, TN was 5% and TP was 6% with the remaining nutrients in woody biomass. The foliar N:P ratio was 8.2, suggesting nitrogen limitation at this site. Based on these results, we estimate that New Zealand mangroves store a total of 0.2–1.1 Mt carbon (C) above ground and 1.06–1.72 Mt C below ground.